Pertuzumab and trastuzumab for HER2-positive, metastatic biliary tract cancer (MyPathway): a multicentre, open-label, phase 2a, multiple basket study. Issue 9 (September 2021) - Javle, Milind; Borad, Mitesh J; Azad, Nilofer S; Kurzrock, Razelle; Abou-Alfa, Ghassan K; George, Ben; Hainsworth, John; Meric-Bernstam, Funda; Swanton, Charles; Sweeney, Christopher J; Friedman, Claire F; Bose, Ron; et al.
Summary: Background: Systemic therapies for metastatic biliary tract cancers are few, and patients have a median overall survival of less than 1 year. MyPathway evaluates the activity of US Food and Drug Administration-approved therapies in non-indicated tumours with potentially actionable molecular alterations. In this study, we present an analysis of patients with metastatic biliary tract cancers with HER2 amplification, overexpression, or both treated with a dual anti-HER2 regimen, pertuzumab plus trastuzumab, from MyPathway. Methods: MyPathway is a non-randomised, multicentre, open-label, phase 2a, multiple basket study. Patients aged 18 years and older with previously treated metastatic biliary tract cancers with HER2 amplification, HER2 overexpression, or both and an Eastern Cooperative Oncology Group performance status of 0–2 were enrolled from 23 study sites in the USA and received intravenous pertuzumab (840 mg loading dose, then 420 mg every 3 weeks) plus trastuzumab (8 mg/kg loading dose, then 6 mg/kg every 3 weeks). The primary endpoint was investigator-assessed objective response rate according to Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1. The primary outcome and adverse events were analysed in all patients who received at least one dose of pertuzumab and trastuzumab. This trial is registered with ClinicalTrials.gov, NCT02091141, and is ongoing. Findings: 39 patients enrolled in the MyPathway HER2 biliary tract cancer cohort between Oct 28, 2014, and May 29, 2019, were evaluable for anti-tumour activity by the March 10, 2020, data cutoff date. Median follow-up was 8·1 months (IQR 2·7–15·7). Nine of 39 patients achieved a partial response (objective response rate 23% [95% CI 11–39]). Grade 3–4 treatment-emergent adverse events were reported in 18 (46%) of 39 patients, most commonly increased alanine aminotransferase and increased aspartate aminotransferase (each five [13%] of 39). Treatment-related grade 3 adverse events were reported in three (8%) of 39 patients, including increased alanine aminotransferase, aspartate aminotransferase, blood alkaline phosphatase, and blood bilirubin. Serious treatment-emergent adverse events were observed in ten (26%) of 39 patients, of which only abdominal pain occurred in more than one patient (two [5%] of 39). There were no treatment-related serious adverse events, treatment-related grade 4 events, or deaths. Interpretation: Treatment was well tolerated in patients with previously treated HER2-positive metastatic biliary tract cancer. The response rate is promising for the initiation of randomised, controlled trials of pertuzumab plus trastuzumab in this patient population. Funding: F Hoffmann-La Roche–Genentech.